Normal Glypican-3 Serum Levels Do Not Eliminate the Risk of Hepatocellular Carcinoma - Agnieszka Lembas; Tomasz Mikuła; Magdalena Suchacz; Joanna Kozłowska; Szymon Barczak; Barbara Badura; Alicja Wiercińska-Drapało (Galician Medical Journal, 2024)
Introduction. Hepatocellular carcinoma (HCC) is a malignancy that primarily affects patients with liver cirrhosis. Early diagnosis is crucial for improving patient outcomes.